Implementasi Tutorial Berbasis Deep Dialogue Dan Critical Thinking Dalam Tutorial Pendidikan Matematika 2 Pada Mahasiswa S-1 PGSD Pokjar Ngawi - Tresnaningsih, Sri; Dwikoranto, Dwikoranto (JURNAL AGRI-TEK, 2014)
Improving activities of tutorial require to apply correct strategy of tutoring. Problem that will be solved is how to implement the deep dialogue and critical thinking (DD/CT) in tutorial activities and student achievement improvement at subject of mathematics2nd and also student response by applying the DD/CT in tutorial. Target of the research is to describe the implementation form of DD/CT in tutorial activities and improvement of learning achievement, and also student response with applying of DD/CT in tutorial. Device research of development adoption of four-D model from Thiagarajan. . Research subject is students of S-1 PGSD group Ngawi.. Result learn in very good category (RTT-1: 85,0; RTT-2: 89,0; and RTT-3: 90,5) and mount each;every phase ( 4,71% and 1, 70%).Keywords: tutorial, dialogue deep, thinking critical.